Investigation of the co-metabolic transformation of 4-chlorostyrene into 4-chlorophenylacetic acid in Pseudomonas fluorescens ST - Stuhr, Anna; Hofmann, Sarah; Schlömann, Michael; Oelschlägel, Michel (Biotechnology reports (Amsterdam, Netherlands), 2018)
•Co-metabolic turnover of 4-Cl-styrene was investigated in a Pseudomonas strain.•Important parameters to optimize this co-metabolism were investigated.•Inhibition by product and under some conditions by the substrate were revealed.•Influence of salt and trace elements on the inhibition were proved.•1.4-fold more product in a 18.5-fold shorter reaction time were achieved. The side-chain oxygenation of styrene is able to yield substituted phenylacetic acids from corresponding styrenes by co-metabolic transformation. This co-metabolization was investigated in Pseudomonas fluorescens ST using 4-chlorostyrene as co-substrate. It was shown that non-substituted styrene is necessary to ensure the co-metabolic process. Furthermore, aspects affecting the co-transformation were studied, e.g. cell density, amount of inducer, pH, effects of co-substrate/co-product. It was demonstrated that 4-chlorophenylacetic acid and 4-chlorostyrene are able to inhibit the reaction. But, these inhibitions are influenced by salt and trace elements. Finally, a protocol was established which considers all findings. Therewith, about 6.7 g L−1 co-product were obtained after 451 h. Compared to previous studies, the co-product concentration was improved by the factor 1.4 while the reaction time was decreased by the factor 18.5. The study offers also aspects for prospective improvements in order to establish an efficient way to gain substituted acids without genetic manipulation.